A new species of Palaemon from Cần Giớ District, Vietnam, previously confused with Palaemon sewelli (Kemp, 1925) - Ashelby, C; De Grave, S; Nv, X (Carcinological Society of Japan, 2018)
A new species of Palaemon is described from Cần Giớ District, Vietnam. This species has previously been reported from Vietnam as a colour morph of Palaemon sewelli (Kemp, 1925), to which it is clearly morphologically very closely related. However, the new species can be separated from P. sewelli through the position of the branchiostegal tooth relative to the branchiostegal groove, the shape of the suborbital lobe, a hirsute carapace and abdomen and the colour pattern of living individuals. The description of this new species brings the number of species of Palaemon known from Vietnam to eleven species.